Efektivitas Bimbingan Karier Virtual untuk Mengembangkan Employability Skills Siswa - Muhammad Amirullah; Aswar Aswar; Suciani Latif; Zulfikri Zulfikri (STKIP Andi Matappa, 2023)
This study aims to determine the effectiveness of virtual career guidance based to enhance the employability skills of Vocational High School Students in covid-19 era. This study used a quantitative approach with a quasi-experimental research design. The sample in this study was taken randomly (random sampling) using a convenience sampling technique. The results of the study show that virtual career guidance was effective in improving the employability skills of Vocational School Students. Based on a review of every aspect, virtual career guidance was effective for improving cognitive, affective, and psychomotoric aspects of the employability skills for Vocational High School students in covid-19 era.